Growth And Yield Of Cassava Leaves To The Dose Of Manure And The Position Of Planting Stem Cuttings - Maryana Maryana; Suwardi Suwardi (Universitas Pembangunan Nasional Veteran Yogayakarta, 2022)
The aim of the research was to determine the growth and yield of cassava leaf at the best dose of manure and planting position of cassava stem cuttings. The location of the research was carried out in the Garden of the Faculty of Agriculture UPN